Features of Written Existence of Charm Tradition in Ulyanovsk Volga Region - A. E. Kalashnikova (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The features of the written existence of charm tradition are considered. The texts from the so-called “cherished notebooks,” which are understood as a kind of manuscript collections created by Russian peasants in the territory of the Ulyanovsk Volga region, mainly by women, in the second half of the 20th - early 21st centuries, are analyzed. It is shown that these notebooks include primarily texts intended for home worship: prayers, Psalms, spiritual verses, etc. It is noted that in some of them there are also traditional charms and prayers that functioned as charms. The material for this research was “cherished notebooks” collected in the period from 1995 to 2008 during folklore expeditions of the Department of Literature of Ulyanovsk State Pedagogical University named after I. N. Ulyanov and stored in the archive of scientific and educational center “Traditional culture and folklore of the Ulyanovsk Volga region.” This article presents the results of the analysis of data on the owners of “cherished notebooks”: the division by sex and age. The geography of this tradition is reported. The content and structure of notebooks are characterized. Attention is paid to the typology of charms recorded in the “cherished notebooks.”